Analysis of Retirement Preparation Program on Retirement Readiness in the State Civil Services at the State Prosecutor of Palembang - Dea Rosa Karina; Trisninawati Trisninawati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Retirement or retirement is the final stage of the service of a Civil Servant (PNS) where at this stage, employees will leave their careers, leave attachments to the organization and face the pressures of retirement physically, psychologically and socially. Retirement is something that will definitely be experienced by every worker and cannot be avoided for a worker, therefore there needs to be careful preparation related to the retirement preparation program, so that the employees of the State Civil Apparatus (ASN) can prepare their employees to face the future. pension. The purpose of this study was to determine how the pension program of State Civil Apparatus (ASN) employees towards retirement readiness at the Palembang District Attorney's Office. To Know What to Prepare for ASN Employees at the Palembang State Prosecutor's Office, in Preparing for Retirement Preparation. The method used in this study is the quantitative method by distributing questionnaires to 72 respondents from the Palembang District Attorney's Office. The results of this study indicate, the level of retirement readiness program of the participants of the retirement preparation program can be categorized as very good with the responses of the respondents of the retirement preparation program participants who have financial material readiness, physical readiness, metal and emotional readiness and the readiness of the whole family. Therefore, it can be interpreted that the participants of the retirement preparation program have a very good level of retirement readiness when viewed from the pension program variables.